PENGARUH PENGGUNAAN MEDIA MUSIK DAN LIRIK TERHADAP KREATIVITAS DAN HASIL BELAJAR GEOGRAFI DIKELAS XI MADRASAH ALIYAH NEGERI PURBALINGGA - Nurfasani, layla Ramdhan (2016)
Musikmemberikanbanyakmanfaatuntukanaksepertimerangsangpikiran, kreativitas, memperbaikikonsentrasi, meningkatkanaspekkognitifhinggamembangunkecerdasan.Penelitianinibertujuanuntukmengetahuibagaimanapengaruh media musikdanlirikterhadapkreativitasdanhasilbelajargeografi.Masalah yang diangkatdalampenelitianiniadalahkurangnyavariasidalampenggunaan media dalampembelajarangeografi di Madrasah Aliyah NegeriPurbalinggasehinggakreativitasdanhasilbelajargeografimenjadikurangmaksimalterutamapadamateripokokpelestarianlingkungandanpembangunanberkelanjutan.PenelitianinimerupakanrancanganpenelitianKuasiEksperimen, denganalatpengumpul data berupates, observasidanwawancara.Teknikanalisis data menggunakanmetodeanalisisfrekuensidanujiTest Of Significance terhadapmean differencess.Hasilpenelitianmenunjukkanbahwa: (1)dengan media musikdanlirikkreativitaspesertadidikmenjaditinggidibandingkandenganpembelajarandenganmenggunakan media gambar yang kriterianyamasukdalamkategorisedang . Padaujibedakreativitaspesertadidik di kelaseksperimendankontroldidapatkanhasilsebesar ±3,881yang menunjukkanbahwaterdapatperbedaandanpengaruh yang meyakinkanantaraperlakuan yang diberikan di kelaseksperimendankelaskontrol. (2), pembelajarandenganmenggunakan media musikdanlirik juga terbuktibisamemberikanpeningkatanhasilbelajar yang bagipesertadidikdibandingkandengan media pembelajarangambarterbuktidarihasilperhitungandananalisis data yang menunjukkanbahwaterdapatperbedaannilaihasilbelajarpesertadidik di kelaseksperimendankontrol. Padakelaseksperimenpeningkatan N-gain daripreteskeposttespadamateripertamadanmaterikeduamasukdalamkategori"sedang" Materipertamadengan N-gain sebesar 0,52 dengannilaiujibeda yang signifikansebesar ±6,810, materikeduasebesar 0,53 dengannilaiujibeda yang signifikansebesar ±3,338.Padakelaskontrolpeningkatan N-gain daripreteskeposttespadamateripertamadanmaterikeduamasukdalamkategori "rendah" sebesar 0,11 dengannilaiujibeda yang signifikansebesar ±2,429, materipertamasebesar 0,05 dengannilaiujibeda yang signifikansebesar ±1,621. Berdasarkanhasil yang diperolehtersebutmenunjukkanbahwapembelajarandenganmenggunakan media musikdanlirikterbuktimampumemberikanpengaruh yang baikpadakreativitasdanhasilbelajarpesertadidiknya, sehinggapenggunaan media musikdanlirikdalampembelajarangeografisangatdianjurkankarenamelaluimusikdanlirikpesertadidikdapatbelajardenganlebihmenyenangkandanbermakna, kreativitaspesertadidikbisaterpacudanhasilbelajar yang baikbisadidapatkan. Sangatdianjurkanuntukmenciptakankaryamusikdanliriksendiri agar materipembelajaran yang akandiajarkanbisadisesuaikandenganlirik di dalammusiktersebut. ;--- Music gives many benefits for children such as stimulating their mind , creativity , improve concentration , and cognitif aspect to build intelligence. This research aims to determine how the media of music and lyrics influences the creativity and learning outcomes Geography in XI grade students. The issues raised in this research is the less variety of using media, especially in the teaching of Geography in Madrasah Aliyah NegeriPurbalingga so that creativity and learning outcomes Geography becomes less than the maximum, especially on the subject matter of environmental conservation and sustainable development. This study is a Quasi-Experimental research design, which is a form of experiment which main characters don't use random assignment, but instead uses existing group in this case is a class that already exists. Data collected with test, observation and interviews. Data were analyzed using frequency analysis and methods Test Of Significance to mean differencess. Data were analyzed using frequency analysis and test methods Test Of Significance to mean differencess. The results showed that: (1) with media of music and lyrics creativity of learners to be high compared to learning by using media of images that the criteria included in the medium category. In different tests the creativity of learners in class of exsperimen andclass of control is ± 3,881obtained results show that there are differences and convincing effect between the treatment given in the experimental class and control class. (2) learning using media of music and lyrics has been shown to provide improved learning outcomes for learners compared with media of image is proven from the results of calculations and data analysis show that there are differences in the value of the study of students in the experimental class and control. The experimental class N-gain improvement from pretest to posttes the first material and the second material into the category of "moderate" first material with N-gain of 0.52 with a significant difference test value of ± 6.810, 0.53 with a second material a significant difference test value of ± 3.338. In the control class N-gain improvement from pretest to posttes the first material and the second material into the category of "low" value of 0.11 with a significant difference test of ± 2.429, the first material of 0.05 with a significant difference test value of ± 1.621. Based on the results obtained showed that learning by using media of music and lyrics proved capable of providing a good influence on creativity and learning outcomes of students, so that the use of media music and lyrics in learning geography is highly recommended because with music and lyrics students can learn more joyfuland meaningful, the creativity of student can be motivated and good study results can be obtained. Highly recommended for creating their own musical works for teaching materials that will be taught can be adjusted with the lyrics in the music.